2009
DOI: 10.1021/jp8031379
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Bonding, and Relative Stability of the Ground and Low-Lying Electronic States of CuO2. The Role of Exact Exchange

Abstract: The C(2v) and C(s) ground and low-lying states of doublet CuO2 are examined for a series of different density functionals (pure, hybrid, and meta-hybrid) and CCSD(T) methods. The effect of changing the B3LYP functional a0 parameter is also explored. CCSD(T) results at the complete basis set limit show that the relative stability of the different electronic states is 2A(2)(C(2v)) < 2A''(Cs) < 2B(2)(C(2v)) < 2A'(C(s)) 2A(1)(C(2v)) < 2B(1)(C(2v)). Unlike CCSD(T), all DFT methods analyzed in this work erroneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…Although there are well known deficiencies with the B3LYP functional (particularly for excited states63), there are plenty of studies of transition metal clusters (neutral and charged) for which the B3LYP/LANL2DZ basis set has been used successfully 6468. For TiO 2 and TiO, Qu and Kroes64 found (in comparison to experiment) vibrational frequencies accurate to about 60 wavenumbers, ionization energies accurate to 0.2 eV, and electron affinities accurate to 0.2 eV.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are well known deficiencies with the B3LYP functional (particularly for excited states63), there are plenty of studies of transition metal clusters (neutral and charged) for which the B3LYP/LANL2DZ basis set has been used successfully 6468. For TiO 2 and TiO, Qu and Kroes64 found (in comparison to experiment) vibrational frequencies accurate to about 60 wavenumbers, ionization energies accurate to 0.2 eV, and electron affinities accurate to 0.2 eV.…”
Section: Methodsmentioning
confidence: 99%
“…18 and its structural isomer (where Cl is bonded perpendicular to the pyridine plane). The spin density on copper can vary strongly, is dependent on the DFT method chosen, 103,104 and in our example it ranges from 0.57 using pure DFT functional to 0.93 for HF. As a matter of fact, the spin density on copper is linearly dependent on the amount of exact exchange admixture to the (hybrid) functional.…”
Section: Part 2: Biomimetic Systemsmentioning
confidence: 98%
“…In these hybrid DFT benchmarks, we fixed a x = 1 À a 0 in eqn (1) but kept the correlation contribution with a c = 0.81 unchanged. The a x = 1 À a 0 convention is already a common choice used in many hybrid functionals [56][57][58][59] such as Becke's B1 convention 57 (in a separate study, we carried out calculations with a x fixed to the original 0.72 value recommended by Becke and found that the error in excitation energies was larger by 0.02 eV compared to the a x = 1 À a 0 convention). It is also worth noting that the set of parameters a 0 = 0.5 and a x = 1 À a 0 = 0.5 yields a functional similar to the BHHLYP functional (a c = 0) with the exception that our choice has an extra correlation contribution due to the DE c,LYP term.…”
Section: Conventional Hybrid Functionalsmentioning
confidence: 99%